To find the equation of the new line after translating the original line \( y = 3x + 2 \) one unit to the right and two units up, we can follow these steps:
-
Translating the line one unit to the right:
- To shift a line \( y = mx + b \) to the right by \( h \) units, we replace \( x \) with \( x - h \). Here, \( h = 1 \), so the new equation becomes:
\[ y = 3(x - 1) + 2 \] \[ y = 3x - 3 + 2 \] \[ y = 3x - 1 \]
- To shift a line \( y = mx + b \) to the right by \( h \) units, we replace \( x \) with \( x - h \). Here, \( h = 1 \), so the new equation becomes:
-
Translating the line two units up:
- To shift the line \( y = mx + b \) up by \( k \) units, we add \( k \) to the entire equation. Here, \( k = 2 \), so we add 2 to the last equation: \[ y = 3x - 1 + 2 \] \[ y = 3x + 1 \]
Thus, the equation of the new line after the translation is \( y = 3x + 1 \).
Therefore, the correct response is: y = 3x + 1